Accumulation of Microplastics and Histological Analysis on Marine Fish from Coastal Waters of Baru and Trisik Beaches, Special Region of Yogyakarta: 10.32526/ennrj/21/202200207 - Putri, Raden Roro Risang Ayu Dewayani; Retnoaji, Bambang; Nugroho, Andhika Puspito (Environment and Natural Resources Journal, 2023)
River flow to the sea is regarded as a pathway for the dispersion and pollution of microplastics. The hydrodynamics of the coastal water of Baru and Trisik Beaches may increase microplastic concentrations in this estuarine-marine area. This research evaluated the microplastic concentration in surface seawater and microplastic accumulation in consumed marine fish and performed histological analysis on the demersal marine fish intestine under natural exposure. Sample collection was carried out at 12 stations with three replications. The microplastics analysis was performed on marine fish (dorsal muscle, gills, and gastrointestinal tract) and seawater, and microplastic characterization was based on physical and chemical characteristics. Environmental parameters for statistical analysis included air and water temperature, pH, dissolved oxygen, and salinity of seawater. Histological analysis of the intestine was performed on fish from three stations with two demersal fish species. The latter analysis included the length of the villi, the depth of the crypt cells, epithelial denudation with hematoxylin-eosin staining, and the number of goblet cells with periodic acid Schiff alcian blue staining. The results showed that the microplastic concentration was distributed throughout the fish sample for each of the stations. Microplastic concentrations for surface seawater showed the same pattern as marine fish. Microplastic accumulation in marine fish indicated the transfer of microplastic particles to various organs in the fish’s body. The histological analysis indicated, microplastic internalization in the intestine tissue, damaging intestinal structures. Further research is needed as consuming marine fish contaminated by microplastics may present increasing health risks.